Manajemen Nonfarmakologis dalam Mengurangi Resiko Konstipasi pada Pasien Ortopedi - Elvina Elvina; Masfuri Masfuri; I Made Kariasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to evaluate the results of published studies related to nonpharmacological management to reduce complaints of constipation in orthopedic patients. The research method used was Systematic Review which was carried out through a search strategy in 9 electronic databases with the keywords (orthopedic patient OR orthopedic patient) AND (nonpharmacological management OR nonpharmacological therapy) AND (constipation OR obstipation). The results showed that there was various nonpharmacological management used to treat and prevent the severity of constipation in orthopedic patients, including interventions such as chewing gum, abdominal massage, acupressure, hydrotherapy, biofeedback therapy, and nursing interventions based on the patient's active involvement in care. Various nonpharmacological strategies are used to treat constipation in orthopedic patients, and the best method to treat constipation in orthopedic patients cannot be ascertained due to the variety of instruments used and differences in sample characteristics in each study. Selected articles were assessed for quality using the Critical Appraisal Skill Program (CASP) guidelines. The six reviewed articles obtained that the range of patients who were given nonpharmacological interventions was â‰¥ 18 years. Instruments for measuring the incidence and severity of constipation are the Constipation Assessment Score, ROME III, Bristol Scale, Rasmusen measuring scale, Constipation Score Method, and Constipation Risk Assessment Scale. In conclusion, several nonpharmacological therapies can be applied to orthopedic patients to reduce their constipation complaints, thereby reducing the impact of hospitalization on patients and improving their quality of life. Keywords: Constipation, Orthopedics, Nonpharmacological Therapy